MOTIVASI PEMANFAATAN PLATFORM CONNECTED PAPERS SEBAGAI SOLUSI CERDAS PENCARIAN LITERATUR ILMIAH - Bakkara, Viona Febiyola; Zulaikha, Sri Rohyanti (Indonesian Journal of Library and Information Science, 2024)
The purpose of the study is to explore the motivation for using the Connected Papers platform as a smart solution in the search for scientific literature. In the ever-evolving information age, researchers are often faced with the challenge of finding and organizing relevant literature. The research method uses a qualitative method by collecting data through interviews and surveys to students of S1 Library Science UIN Ar-Raniry Banda Aceh, and students who utilize the Connected Papers Platform, active users of Connected Papers among students and researchers. The research subjects were 8 students from 100 students of the 2021 S1 Library Science Study Program of UIN Ar-Raniry Banda who utilized the Connected Papers Platform. The object of the research is Library Science students of the class of 2021 who utilize the Connected Papers Platform. Data analysis techniques are carried out through the process of data reduction, data presentation, and drawing conclusions. The results of the study show that students of the library science study program of UIN Ar-Raniry Banda Aceh have experienced ease of access, efficiency in finding literature, and the ability to see the relationship between research as the main motivation. In addition, the platform is also considered a tool that supports the process of analyzing and synthesizing information, which is very important in the preparation of literature reviews. This finding is expected to provide insight for researchers and academics in utilizing modern technology to improve the quality of research and scientific development.